Young children thinking - Yardley, Alice (New York : Citation Press, 1973)
'This is a book to be treasured. This deeply respected pioneer brings together major research literature, theoretical understanding and practical help. She does so in a way that demonstrates her love and commitment in working with young children and helping them to have rich lives intellectually and with personal fulfillment'.
Includes index.
Keywords: Cognition in children; Child psychology